Wpływ Jana III Sobieskiego na sejmiki ziemskie – próba interpretacji zjawiska - Kołodziej, Robert (Władza i polityka w czasach nowożytnych. Dyplomacja i sprawy wewnętrzne, 2020)
Jan III Sobieski was active in the domestic policy. He tried to influence pre-parliament dietines so they would elect the King’s sympathetic parliamentarians and to take into account instructions advantageous to the Court. There was lot of assembly in Polish-Lithuanian Commonwealth and the King needed many supporters – senators and local noble elites. However, he had a wide range of possibilities on how to win them. People trusted by the Court attended the dietines personally or through their family and political friends. They reported to the King on the results of deliberations, made sure people elected as deputies were recommended by the Monarch and there weren’t disadvantages for the Court in an instruction. Of course, the Court didn’t win the political fight everywhere. Sometimes a compromise with the opposition was necessary. Occasionally Court’s supporters interrupted a dietine to not allow the opposition to win. The King convened often a second dietine, which was sometimes held in secret, with a small circle of trusted people. The methods used by the King weren’t different from methods of opposition and Sobieski took advantage of the cracks in the parliamentary system of Polish-Lithuanian Commonwealth.